Preventive intervention actions to address bullying based on the draft School Peaceful Coexistence Law (Revista Electrónica REDINE, 2022)
This investigation, as a result of a documentary review, proposes from the Draft Law for Peaceful School Coexistence (2022), a series of preventive intervention actions focused on minimizing the effects of bullying, as a destructive multifactorial phenomenon of the positive school climate, of interpersonal relationships and of the coherent performance of the pedagogical action. It is then understood that promoting the creation of positive psychosocial conditions favors the subject in formation to achieve social, affective and emotional development throughout the life cycle, as well as the full development of their personality, factors on which their competitive disposition depends to opportunely face the challenges of the context in which they live.
Keywords: bullying; coexistence; psychosocial integrity; psychological well-being; personal development